The Impact of Students’ Academic Self-Confidence on the English Learning Process in the Post-Pandemic Era - Saidah, Saidah (Journal of Languages and Language Teaching, 2024)
The pandemic has had a significant impact on education. Students' academic self-confidence has likely been affected as well. The transition to current onsite learning may have contributed to feelings of anxiety and decreased their self-confidence. This study aimed to measure student’s academic self-confidence and its impact on their English learning process. It was a descriptive research design with quantitative questionnaires distributed to 100 male and female students of Islamic broadcasting communication study program of IAIN Kediri. The result revealed that few students had low academic self-confidence when they had to argue in English with their classmates. Most students had high academic self-confidence to carry out other activities in the class and outside the class in finding English learning goals. Furthermore, students’ academic self-confidence highly affects their autonomous learning so that makes students able to work and learn English independently by using computers and the internet. It makes learning English more enjoyable for them as well. In addition, most of the students agreed that their self-confidence caused them to make regular plans to review English lessons, actively participate in English learning, ask English-related questions to classmates and lecturers, to share ideas and opinions in English group discussions, and also do English presentations well. The results of this study can be a consideration for English teachers to pay more attention to students who still have low confidence by applying teaching strategies that increase students' self-confidence.